The development of a collaborated gamified e-quiz and strategy game mobile application to increase students' motivation and continuance usage intention - Roslan, Rosfuzah; Ahmad Fauzi; Mohd Ayub; Ghazali, Norliza; Zulkifli, Nurul Nadwa (Association for Researcher of Skills & Vocational Training, 2021)
Gamification has been taken seriously as an educational approach that is able to facilitate learning, encourage motivation and engagement, improve learner participation and lesson interactivity, and stimulate learners towards the expansion of their knowledge. Given the changes in the digital world over the last decades, students of the current generation expect technology to be used in advancing their learning, requiring a need to change traditional passive learning methodologies to an active multisensory experimental learning methodology. This study introduced, ‘Kingdom Quizzes’ (KQ) a gamified e-quiz mobile application which was previously known as ‘Quiz Seeker’ mobile application as an assisting tool in teaching and learning. The purpose of the development of KQ is to enhance the students’ motivation in academic task as well as retaining the users of a gamified e-quiz. KQ is divided into two interconnected modules; (i) quiz module, and (ii) game module. This product focused on the ‘reward’ element resulted from ranking in the quiz session in which it will be passed on to the next game session. The marks and rank that the students gained in the quiz session will reward them with coins or ‘life’ item in their game inventory. This creates a sense of ‘motivation’ in students to do well in their quiz sessions as well as creating a ‘continuance intention’ in using the product which means high tendency to keep executing e-quiz for various other subjects. Based on the survey conducted with 141 respondents, KQ basically managed to fulfill the objectives of the product development which were to increase the students’ (i) motivation as much as 93.7% and (ii) continuance intention in using the gamified e-quiz application as much as 88.72%. Based on the Pearson’s correlation analysis, motivation has a significantly moderate relationship with continuance usage intention, (r = 0.607**, p = 0.000). Moreover, the multiple regression analysis using the enter method also proved that predictor motivation contributed 36.9% towards the continuance intention of the students to use KQ. The product does not only manage to be adopted among the targeted audiences, but based on this study it has a huge future potential as the choice for mobile-based quick formative assessment.